PENGELOLAAN KEUANGAN DESA BATULAYA, KABUPATEN POLEWALI MANDAR DALAM MENERAPKAN PRINSIP GOOD GOVERNANCE - Andi Nur Fiqhi Utami; Aco Nata Saputra (Universitas Sulawesi Barat, 2021)
The purpose of this research is to determine the application of Good Governance principles in the management of village finances in Batulaya village. This is a case study research. Data were obtained by conducting interviews and documentation. The data analysis technique used began by describing the characteristics of the interviewees, comparing theory with the information obtained from the interviewees, comparing theory with the practices obtained from the interpretation of interviews and observations in a comparison table, and ending with drawing conclusions. The results of the study indicate that out of the 9 Good Governance principles, 7 have been implemented, namely the principle of upholding the rule of law, caring for the community, being consensus-oriented, effective and efficient, transparent, responsible and fair, while the other 2 principles have been partially implemented, namely community participation and accountability.